Modern Management of Medical Waste in UNRWA Clinics in Gaza Strip Governorates - Al Ashqar, Nizam Mahmoud; Abu Shuaib, Israa Idris (Journal of Risk and Crisis Management, 2019)
This study aimed to identify the reality of modern medical waste management in UNRWA which include: First: sorting operations, which is the separation of the normal medical waste from the hazardous medical waste at the source of its production and packaging in bags as classified by the World Health Organization. Second: collection operations, which is the collection of medical waste in tightly sealed bags up to three quarters and internal transport processes by providing suitable vehicles for the transport of medical waste from the clinics to the temporary storage room. Third: storage operations, the allocation of a room as a collection point for waste. Fourth: the final disposal, where the produced medical waste are quantified by weighing then transported by Ministry of Health trucks in order to be treated and final disposed. The study also aimed to identify the occupational safety procedures for workers against medical waste hazards, in order to provide recommendations regarding the management and safe handling of medical waste, to protect the worker from infection accidents and the dangers of medical waste, reduce the incidence of errors, accidents during the management of medical waste and maintain environmental safety. The study relied on several methods of collecting information, including field visits, UNRWA reports and manuals of waste management.
Keywords: Medical waste; Waste Management; Hazardous waste; Biohazards; Infection; JICA